2013
DOI: 10.1111/dsu.12233
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Split-Face Study Comparing Conventional Methyl Aminolevulinate-Photodynamic Therapy (PDT) With Microneedling-Assisted PDT on Actinically Damaged Skin

Abstract: Microneedling-assisted PDT is a safe and effective method and can produce superior cosmetic results to conventional MAL-PDT for improving photodamaged skin. Further larger prospective studies are needed to determine whether the addition of MN decreases actinic keratosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 5 publications
(13 reference statements)
1
53
0
5
Order By: Relevance
“…One study reported infections with herpes simplex virus (HSV), but it was unclear if these patients had acne scarring (Aust et al, 2008a). Reports of HSV infections have been noted in other articles (Fernandes, 2005, Torezan et al, 2013) and oral acyclovir was given to patients with a history of HSV in at least one study including patients with acne scarring (Alam et al, 2014). …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…One study reported infections with herpes simplex virus (HSV), but it was unclear if these patients had acne scarring (Aust et al, 2008a). Reports of HSV infections have been noted in other articles (Fernandes, 2005, Torezan et al, 2013) and oral acyclovir was given to patients with a history of HSV in at least one study including patients with acne scarring (Alam et al, 2014). …”
Section: Resultsmentioning
confidence: 98%
“…Fine needles puncture the skin, resulting in increased dermal elastin and collagen, collagen remodeling, and thickening of the epidermis and dermis (Aust et al, 2008a, Aust et al, 2010a, Aust et al, 2010b, Aust et al, 2011, Fabbrocini et al, 2011a, Fernandes, 2005, Fernandes and Signorini, 2008, Kim et al, 2011, Park et al, 2012, Schwarz and Laaff, 2011). Additionally, skin needling creates small channels, which increase the absorption of topically applied preparations (Badran et al, 2009, Kalluri et al, 2011), a property which has been used in various dermatological treatments (Bencini et al, 2012, Budamakuntla et al, 2013, Clementoni et al, 2010, Fabbrocini et al, 2011b, Fabbrocini et al, 2014a, Kang et al, 2008, Torezan et al, 2013, Yoon et al, 2008, Yoon et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The most recent studies include use of keratolytics, curettage/debulking, tape stripping, microdermabrasion, and laser ablation 21,45,46. One split-face study demonstrated slightly superior efficacy and long-term improvement of actinic keratoses when using microneedling as a delivery system 47. Use of microneedling in SCC in situ and BCC failed to demonstrate either increased fluorescence uptake or clinical superiority.…”
Section: Light Source and Methods Of Deliverymentioning
confidence: 99%
“…In one study, Torezan [37] et al reported treating ten patients with facial photodamage and actinic keratoses with MAL-PDT or microneedling-assisted PDT. In this prospective, randomized, split face study, they were able to demonstrate the effectiveness of both modalities in the treatment of photodamage, mottled pigmentation, roughness and sallowness, with the superior efficacy of microneedling-assisted PDT compared to MAL-PDT alone on fine lines at day 30.…”
Section: Clinical Applicationsmentioning
confidence: 99%